2023
DOI: 10.1101/2023.03.02.23286669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of a digital application to enhance communication and triage between care homes and National Health Service community services in the United Kingdom: a qualitative evaluation

Abstract: Recent years have seen a rise in digital interventions to improve coordination between care homes and NHS services, supporting remote sharing of data on the health of care home residents. Such interventions were key components in the response to the COVID-19 pandemic. This paper presents findings from the qualitative component of an evaluation of an implementation of the HealthCall Digital Care Homes application, across sites in northern England. The implementation commenced prior to the pandemic and continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Improved communication between care home staff and the NHS, including NHS community nursing services, provides greater opportunity for joint decision making on the delivery of optimal care for residents, which we found led to a reduction in ED attendances and hospital admission. The associated qualitative study undertaken alongside this quantitative analysis [ 5 ] found that additional input from a multi-disciplinary team improves the confidence of care home staff by providing greater monitoring, and earlier identification of deterioration. This in turn may impact on the reduced length of hospital stay due to earlier detection and prompt management of illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved communication between care home staff and the NHS, including NHS community nursing services, provides greater opportunity for joint decision making on the delivery of optimal care for residents, which we found led to a reduction in ED attendances and hospital admission. The associated qualitative study undertaken alongside this quantitative analysis [ 5 ] found that additional input from a multi-disciplinary team improves the confidence of care home staff by providing greater monitoring, and earlier identification of deterioration. This in turn may impact on the reduced length of hospital stay due to earlier detection and prompt management of illness.…”
Section: Discussionmentioning
confidence: 99%
“…One of the solutions provided is the Health Call Digital Care Homes Application (app), designed for use by staff in care homes [ 3 ]. A primary goal of the app is to reduce avoidable secondary care for the residents in the homes, through timely access to clinical advice ( Box 1 ) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Impact of Health Call on non-zero costs and the probability of zero monthly costs in the form of odds ratio (OR) for zero cost models and relative risks for the magnitude of costs model (RR Improved communication between care home staff and the NHS, including NHS community nursing services, provides greater opportunity for joint decision making on the delivery of optimal care for residents, which we found led to a reduction in ED attendances and hospital admission. The associated qualitative study undertaken alongside this quantitative analysis [5] found that additional input from a multi-disciplinary team improves the confidence of care home staff by providing greater monitoring, and earlier identification of deterioration. This in turn may impact on the reduced length of hospital stay due to earlier detection and prompt management of illness.…”
Section: Discussionmentioning
confidence: 99%